InfoDesign - Information Design - Spinillo, Carla; Farias, Priscila (InfoDesign, 2004)
Information design can be characterized as the placing of questions related to the fruition of its products as its central issue. That being the case, certain questions are brought forth by the practice and research of information design, e.g. the experience of the user as a determining aspect of the project; design as a factor to facilitate inclusion (technological, social) and the possible forms in which design contributes to the general well-being. This can be expressed not only by planning more efficient sign systems, but also by research concerned with the better understanding of day-to-day documents (medicine information pamphlets, manuals, forms); and the development of computer interfaces, which do not intimidate or exclude its users, as well as any other field where communicative efficiency is an important factor; and where the construction of knowledge, rather than persuasion, is the desired route in which to obtain this efficiency. More than being a new applied area or division in the field of knowledge, information design represents a new posture that has the tendency of influencing the practice and process of design, with clear consequences for its products and for the people who use them. The fact that this was a common posture in the thoughts and actions of a representative group of researchers in Brazil resulted in the formation of the Brazilian Society of Information Design, and the organization of the first International Conference of Information Design. The creation of InfoDesign - The Brazilian Journal of Information Design can be seen as an extension of these efforts. With this publication, a permanent space has been created for disclosing proposals and research results, reflections, critical viewpoints, as well as reviews, interviews and events that contribute to the promotion and consolidation of information design. In this opening edition of InfoDesign, the articles - all with differing approaches and themes - deal with "information design of inclusion", in which the information readers/users must steer their way through decisions taken during the design process in order to achieve successful communication. Initially, we present the article by Judy Gregory, which defends the involvement of the reader with the represented topic/message as a prerogative for the effective design of information. She argues clearly and precisely exactly how the involvement level of an individual/audience is a determinant in the motivation to read information/education material, whether it is a pamphlet, or an instruction manual. Judy highlights the importance of this aspect in order to define the communicative strategy adopted by the information designer, which according to the writer, and depending on the involvement profile of the reader/audience, may be argumentative/informative, and/or emotional/entertainment. The theoretical arguments are enriched by the discussion of experimental study results with young students concerning motivation in reading information dealing with different themes such as alcohol and meningitis. The questions raised in this article help to expand the effective scope in information design, which should not be restricted to the represented aesthetic and message information quality, but rather encompass in an integrated manner, the motivation and involvement of the reader/public with the theme and the adopted communication vehicle. Following on, in his article concerning instructional design, Franck Ganier also highlights the importance of the information reader/user for the success of the representation of the process messages. Strongly grounded in cognitive psychology and instructional technology, as well as in empirical research, he presents a pragmatic approach to the theme, by means of orientation and established guidelines for producing this type of message. An important contribution to information design contained within Franck's article concerns the cognitive aspects pertinent to reading instructional messages and carrying out the relevant tasks. The discussion of factors such as : the relationship between the representation of instructions and mental representation; the role of memory and inferences in represented actions; corroboration for a greater understanding of how instructional information design can be optimized in order to reach the best performances in carrying out process actions (tasks). Similarly, María de Cossío also places emphasis on the reader/user of information design messages, this time within the scope of virtual space. From an empirical perspective, she discusses the representation of cognitive maps using the results of a study carried out with graphic design students (experienced users of the internet/www) in Mexico and the UK, concerning the navigational aspects of familiar electronic documents. This article is particularly interesting since it presents an information design approach to the empirical research of electronic documents, taking graphic and information aspects into consideration in an integrated form with process or forms of constructing navigational routes in virtual space. This is certainly a methodological contribution to the area. An experimental approach to the design of documents is also adopted by Patricia Fujita in her article in the Undergraduate research section, which is destined towards the production of young researchers in information design. Instructional design is also a theme of this article, related to the study of the efficacy of medicine information pamphlets for older people. The merit of this article is mainly encountered in the social importance of investigating aspects of information design related to the area of health, and primarily focusing on a particularly sensitive and differentiated social group. Also within the social bounds of information design, in the section Points of View, Joaquim Redig deals with the relevance of this area for contemporary society, emphasizing the relevant factors of information design together with the concept of citizenship. Joaquim presents a clear, inspired historical report of information design in Brazil; and from the starting point of "doesn't all design supply information?" establishes a critical/analytical view of receiver and form and time; factors that consider characteristics of information design. This edition also carries a book review of Israel Pedrosa's book "Universo da Cor" (2003) (Universe of Colour) by Regina Lemgruber, and an interview conducted by Stephania Padovani with Jorge Frascara, writer, professor and researcher from the University of Alberta, Canada, who has supplied a substantial contribution to information design. And finally, we would like to emphasize that InfoDesign: The Brazilian Journal of Information Design is not only an editorial initiative but a challenge, which we hope to share with all our readers.